Flame-retardant styrene-based resin composition and molded article
The styrenic resin composition with phosphinate and cellulose polysaccharide additives addresses dispersibility and anisotropy issues, achieving enhanced flame retardancy, low smoke, and color stability, suitable for electronic and home appliance applications.
Patent Information
- Application Number
- JP2021126210
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-07-30
AI Technical Summary
Existing styrenic resin compositions face issues with poor dispersibility of flame retardants, leading to insufficient flame retardancy, black smoke generation during combustion, and anisotropic dimensional accuracy, which affects adhesion to metals and color stability.
A flame-retardant styrenic resin composition comprising 40-92% styrenic resin, 5-30% phosphinate compound, and 3-30% cellulose polysaccharide with specific dimensions, optimized to enhance dispersibility, reduce smoke emission, and improve dimensional accuracy and color tone.
The composition achieves high flame retardancy, low smoke emission, excellent dimensional accuracy, and stable color tone, addressing the limitations of previous technologies while reducing environmental impact.
Smart Images

Figure 0007619906000001 
Figure 0007619906000002 
Figure 0007619906000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a flame-retardant styrenic resin composition and a molded article thereof. [Background technology]
[0002] Styrene-based resins are used in a wide range of applications due to their excellent moldability, dimensional stability, and impact resistance. Among them, polystyrene-based resin compositions with flame retardancy are used in a wide range of applications, including home appliances and office automation equipment, and there is currently a demand for thinner products to reduce size and weight. Conventionally, various flame retardants have been proposed for the purpose of imparting flame retardancy to polystyrene-based resin compositions. Among them, bromine-based flame retardants, which are inexpensive and have a good balance of physical properties, are widely used. However, in recent years, due to the movement to regulate halogen-containing organic compounds, mainly in Europe, there is an increasing demand for flame-retardant resins and flame-retardant resin compositions that do not contain bromine elements. Furthermore, from the viewpoint of carbon neutrality, there is an increasing need to contain bio-based materials.
[0003] As an alternative flame retardant to such bromine-based flame retardants, for example, Patent Document 1 discloses a technique of adding a phosphinate to a thermoplastic polymer. Moreover, Patent Document 2 discloses a technique for improving flame retardancy by adding a flame retardant and cellulose nanofibers to a thermoplastic resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-124466 [Patent Document 2] International Publication No. 2017 / 169494 Summary of the Invention [Problem to be solved by the invention]
[0005] Although the above-mentioned Patent Document 1 describes that flame retardancy can be imparted to a polystyrene-based resin composition, the flame retardant described in Patent Document 1 has poor dispersibility in polystyrene, insufficient flame retardancy, and generates black smoke during combustion, which are problems. In addition, in the technology of Patent Document 2, the flame retardancy is improved by blending the specific flame retardant and cellulose nanofiber described in Patent Document 2 into a polystyrene-based resin composition, but black smoke during combustion of polystyrene cannot be prevented. In addition, since a composite product combining a molded product of a polystyrene-based resin composition with an internal mechanism part or metal, etc., requires dimensional accuracy of the material, if the linear expansion coefficient of a molded product of a polystyrene-based resin composition containing cellulose nanofiber as described in Patent Document 2 shows a large anisotropy between the MD direction and the TD direction, the adhesion to different materials such as metals may be disadvantageous. Furthermore, when the polystyrene-based resin composition is processed, the color turns brown, which is difficult to color in white.
[0006] Therefore, the present invention provides a flame-retardant styrene-based resin composition which reduces the environmental load and has low smoke generation, flame retardancy, dimensional accuracy and excellent color tone. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the present inventors have surprisingly found that a resin composition in which a flame retardant (B) and a specific cellulose polysaccharide (C) are added to a styrene resin in a specific ratio reduces the environmental load and has very high flame retardancy, low smoke generation, dimensional accuracy, and excellent color tone, and have completed the present invention. That is, the present invention is as follows.
[0008] [1] The present invention relates to a styrene-based resin (A) of 40 to 92% by mass, The following general formula (i): [ka] [In the above formula (i), R i1 and R i2are each independently unsubstituted or one or more hydrogen atoms are substituted by R i3 a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by The substituent R i3 is represented by the following formula (ii): [ka] In the above formula (ii), R ii1 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond to another atom. M i is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and protonated nitrogen base, and p + is M i represents the ionic valence of the compound, is a positive integer of 1 to 3, and m i1 is a positive integer between 1 and 3, and n - represents a negative integer of -1, -2, or -3; r represents a positive integer of 1 to 3; |p + ×r|=|n - ×m i1 |. | 5 to 30 mass % of a flame retardant (B) containing a phosphinate compound (b) represented by the formula: The flame-retardant styrene-based resin composition is characterized by containing 3 to 30 mass % of a cellulose-based polysaccharide (C) having an average length of at least one of the minor axis d1 and the major axis d2 of 10 to 80 μm. [2] In this embodiment, the phosphinic acid compound (b) is preferably at least one or more selected from the group consisting of a phosphinic acid salt represented by the following general formula (1) and a diphosphinic acid salt represented by the following general formula (2): [ka] [In the above formula (1), R 11 and R 12are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M 1 is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, + is M 1 represents the ionic valence of the compound, is a positive integer of 1 to 3, and m 1 is a positive integer between 1 and 3, and a=m 1 It is.] The following formula (2): [ka] [In the above formula (2), R 21 and R 22 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; L 23 is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 14 carbon atoms, or an arylalkylene group having 6 to 14 carbon atoms; M 2 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and protonated nitrogen bases, and b + is M 2 represents the ionic valence of the compound, is a positive integer of 1 to 3, and m 2 is a positive integer from 1 to 3, q is a positive integer of 1 or 2, and b×q=2m 2 It is.] [3] In this embodiment, the styrene-based resin (A) preferably contains a styrene-based monomer unit and an unsaturated carboxylic acid-based monomer unit. [4] In the present embodiment, the cellulose polysaccharide (C) preferably contains 20 mass% or less of lignin. [5] In this embodiment, the cellulosic polysaccharide (C) preferably has a hemicellulose content of 1% or more. [6] The present embodiment is preferably a molded article comprising the flame-retardant styrene-based resin composition according to any one of [1] to [5]. Effect of the Invention
[0009] The present invention provides a flame-retardant styrene-based resin composition which reduces the environmental load and has low smoke generation, flame retardancy, dimensional accuracy and color tone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The following describes in detail an embodiment of the present invention (hereinafter referred to as the "present embodiment"); however, the present invention is not limited to the following description and can be implemented in various modified forms within the scope of its gist.
[0011] [Flame-retardant styrene-based resin composition] The flame-retardant styrene-based resin composition of the present embodiment contains 40 to 92 mass% of a styrene-based resin (A) (hereinafter also referred to as component (A)), 5 to 30 mass% of a flame retardant (B) (hereinafter also referred to as component (B)) containing a phosphinate compound (b), and 3 to 30 mass% of a cellulose-based polysaccharide (C) (hereinafter also referred to as component (C)) having an average length of at least one of the minor axis d1 and the major axis d2 of 10 to 80 μm. The phosphinate compound (b) is represented by the following general formula (i): [ka] [In the above formula (i), R i1 and R i2 are each independently unsubstituted or one or more hydrogen atoms are substituted by R i3 a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by The substituent R i3 is represented by the following formula (ii): [ka] In the above formula (ii), R ii1 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond to another atom. M i is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion, and protonated nitrogen bases; + is M i represents the ionic valence, and is a positive integer of 1 to 3; m i1 is a positive integer between 1 and 3, and n - represents a negative integer of -1, -2, or -3, and |p + ×r|=|n - ×m i1 | is represented as . This makes it possible to provide a flame-retardant styrene-based resin composition that is excellent in low smoke generation, flame retardancy, dimensional accuracy and color tone. Each component contained in the flame-retardant styrene-based resin composition will be described below.
[0012] <Styrene-based resin (A): Component (A)> In the flame-retardant styrene-based resin composition of the present embodiment, the content of the styrene-based resin (A) is 40 to 92 mass%, preferably 50 to 90 mass%, and more preferably 60 to 85 mass%, based on 100 mass% of the total amount of the (A), (B) and (C) components. If the content of the styrene-based resin (A) is less than 40 mass%, the moldability decreases, and if it exceeds 92 mass%, the flame retardancy decreases.
[0013] The styrene-based resin (A) that can be used in this embodiment is preferably a resin obtained by polymerizing a styrene-based monomer and, if necessary, one or more selected from other vinyl-based monomers copolymerizable with the styrene-based monomer and rubber-like polymer (a). In other words, the styrene-based resin (A) is preferably a polymer having a styrene-based monomer unit, and more preferably a polymer that essentially contains a styrene-based monomer unit and has, as an optional component, other vinyl-based monomers copolymerizable with the styrene-based monomer unit and / or monomer units of rubber-like polymer (a). The preferred form of the styrene resin (A) in this embodiment is not particularly limited, but specifically includes, for example, a rubber-modified styrene resin in which particles of a rubber-like polymer (a) are dispersed in a polymer matrix containing polystyrene, a polystyrene polymer (polystyrene and / or a polystyrene-unsaturated carboxylic acid polymer, etc.), or a styrene copolymer resin. In addition, a styrene polymer having a syndiotactic structure can also be used as the styrene resin (A).
[0014] <<Polystyrene>> In this embodiment, polystyrene is a homopolymer obtained by polymerizing a styrene-based monomer, and generally available ones can be appropriately selected and used. In addition to styrene, the styrene-based monomer constituting polystyrene includes α-methylstyrene, α-methyl-p-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, and t-butylstyrene, or styrene derivatives such as bromostyrene and indene. Styrene is particularly preferred from an industrial viewpoint. One or more of these styrene-based monomers can be used. Polystyrene typically consists of styrene-based monomer units, although it is not excluded that polystyrene further contains monomer units other than the above-mentioned styrene-based monomer units within a range that does not impair the effects of the present invention.
[0015] <<Rubber-modified styrene resin>> In this embodiment, the rubber-modified styrene-based resin is a resin in which particles of a rubber-like polymer (a) (also referred to as rubber-like polymer (a) particles) are dispersed in a styrene-based resin as a matrix, and can be produced by polymerizing a styrene-based monomer in the presence of the rubber-like polymer (a).
[0016] Examples of the styrene monomer constituting the rubber-modified styrene resin of the present embodiment include, in addition to styrene, α-methylstyrene, α-methyl p-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, and t-butylstyrene, or styrene derivatives such as bromostyrene and indene. Styrene is particularly preferred. These styrene monomers can be used alone or in combination.
[0017] The rubbery polymer (a) particles contained in the rubber-modified styrene-based resin of this embodiment may, for example, encapsulate a resin containing a styrene monomer unit obtained from the above-mentioned styrene-based monomer inside the rubbery polymer (a) particles, and / or may have a resin containing a styrene monomer unit grafted onto the surface of the rubbery polymer (a) particles.
[0018] As the rubber-like polymer (a), for example, a rubber component such as polybutadiene, polyisoprene, natural rubber, polychloroprene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, etc. can be used. The rubber component may also include a form containing polystyrene and / or polystyrene-unsaturated carboxylic acid polymer. Among them, the rubber-like polymer (a) is preferably polybutadiene or styrene-butadiene copolymer. As the polybutadiene, both high-cis polybutadiene having a high cis content and low-cis polybutadiene having a low cis content can be used. In addition, both random structure and block structure can be used as the structure of the styrene-butadiene copolymer. These rubber-like polymers (a) can be used alone or in combination. In addition, saturated rubber obtained by hydrogenating butadiene rubber can also be used.
[0019] Examples of such rubber-modified styrene-based resins include HIPS (high impact polystyrene), ABS resin (acrylonitrile-butadiene-styrene copolymer), AAS resin (acrylonitrile-acrylic rubber-styrene copolymer), and AES resin (acrylonitrile-ethylene propylene rubber-styrene copolymer).
[0020] When the rubber-modified styrene resin is a HIPS resin, the particularly preferred rubber polymer (a) is a high-cis polybutadiene having 90 mol % or more of cis-1,4 bonds. In the high-cis polybutadiene, the vinyl 1,2 bonds are preferably 6 mol % or less, and more preferably 3 mol % or less.
[0021] The content of isomers having a cis-1,4 structure, a trans-1,4 structure, or a vinyl-1,2 structure as the structural unit of the isomeric polybutadiene can be measured using an infrared spectrophotometer and calculated by processing the data using the Morello method.
[0022] The high-cis polybutadiene can be easily obtained by a known production method, for example, by polymerizing 1,3-butadiene using a catalyst containing an organoaluminum compound and a cobalt or nickel compound.
[0023] The content of the rubber-like polymer (a) contained in the rubber-modified styrene-based resin (not including the styrene-based resin as a matrix incorporated in the rubber-like polymer (a) particles) is preferably 3 to 20 mass% and more preferably 5 to 15 mass% relative to 100 mass% of the total amount of the rubber-modified styrene-based resin. If the content of the rubber-like polymer (a) is less than 3 mass%, the impact resistance of the styrene-based resin may decrease. If the content of the rubber-like polymer (a) is more than 20 mass%, the flame retardancy may decrease.
[0024] In the present disclosure, the content of the rubber-like polymer (a) contained in the rubber-modified styrene-based resin is a value calculated using pyrolysis gas chromatography.
[0025] The average particle size of the rubber-like polymer (a) particles contained in the rubber-modified styrene-based resin is preferably 0.5 to 4.0 μm, and more preferably 0.8 to 3.5 μm, from the viewpoints of impact resistance and flame retardancy.
[0026] In the present disclosure, the average particle size of the rubber-like polymer (a) particles contained in the rubber-modified styrene-based resin can be measured by the following method. A 75 nm thick ultrathin section is prepared from the rubber-modified styrene-based resin stained with osmium tetroxide, and a photograph is taken at a magnification of 10,000 times using an electron microscope. In the photograph, the particles stained black are rubber-like polymer (a) particles. From the photograph, the following formula (N1): Average particle diameter=ΣniDri 3 / ΣniDri 2 (N1) (In the above formula (N1), ni is the number of rubber polymer (a) particles having a particle diameter Dri, and the particle diameter Dri is the particle diameter calculated as a circle-equivalent diameter from the area of the particle in the photograph.) The area-average particle size is calculated by the above formula, and is regarded as the average particle size of the rubber-like polymer (a). In this measurement, a photograph is scanned at a resolution of 200 dpi, and the measurement is performed using particle analysis software of an image analyzer IP-1000 (manufactured by Asahi Kasei Corporation).
[0027] The reduced viscosity of the rubber-modified styrene-based resin (which is an index of the molecular weight of the rubber-modified styrene-based resin) is preferably in the range of 0.50 to 0.85 dL / g, more preferably in the range of 0.55 to 0.80 dL / g. If it is less than 0.50 dL / g, there is a risk of a decrease in impact strength, and if it exceeds 0.85 dL / g, there is a risk of a decrease in moldability due to a decrease in fluidity.
[0028] In this disclosure, the reduced viscosity of the rubber-modified styrene-based resin is a value measured in a toluene solution at 30° C. and a concentration of 0.5 g / dL.
[0029] The method for producing the rubber-modified styrene-based resin is not particularly limited, but it can be produced by bulk polymerization (or solution polymerization) in which a styrene-based monomer (and a solvent) is polymerized in the presence of the rubber-like polymer (a), or bulk-suspension polymerization in which the reaction is changed to suspension polymerization during the course of the reaction, or emulsion graft polymerization in which a styrene-based monomer is polymerized in the presence of the rubber-like polymer (a) latex. In bulk polymerization, the rubber-like polymer (a) can be produced by continuously supplying a mixed solution containing the rubber-like polymer (a) and the styrene-based monomer, and optionally an organic solvent, an organic peroxide, and / or a chain transfer agent, to a polymerization apparatus consisting of a complete mixing reactor or a tank reactor and a plurality of tank reactors connected in series.
[0030] <<Styrene-based copolymer resin>> In the present embodiment, the styrene-based copolymer resin is a resin containing a styrene-based monomer unit and other monomers (e.g., unsaturated carboxylic acid-based monomer units) copolymerizable with the styrene-based monomer. For example, when the other monomers are unsaturated carboxylic acid-based monomer units, the styrene-based copolymer resin according to the present invention has a styrene-based monomer unit content of preferably 69 to 98% by mass, more preferably 74 to 96% by mass, and even more preferably 77 to 92% by mass, when the total content of the styrene-based monomer units and the unsaturated carboxylic acid-based monomer units is taken as 100% by mass. By making the content 69% by mass or more, the flowability of the resin can be improved. On the other hand, by making the content of the styrene-based monomer unit 98% by mass or less, it becomes difficult to make a desired amount of an unsaturated carboxylic acid-based monomer unit, which is an example of the other monomer, exist, and it becomes difficult to obtain the effects described below due to these monomer units.
[0031] The unsaturated carboxylic acid monomer in the present embodiment includes an unsaturated carboxylic acid monomer and an unsaturated carboxylic acid ester monomer.
[0032] In the preferred styrene-based copolymer resin of this embodiment, the unsaturated carboxylic acid monomer unit plays a role in improving heat resistance. When the total content of the styrene-based monomer unit, the unsaturated carboxylic acid monomer unit, and the unsaturated carboxylic acid ester monomer unit in the styrene-based copolymer resin is taken as 100% by mass, the content of the unsaturated carboxylic acid monomer unit is preferably 2 to 16% by mass, more preferably 4 to 14% by mass, and even more preferably 8 to 13% by mass. By making the content 2% by mass or more, the dispersibility of the (B) component is improved and the heat resistance can be further improved. On the other hand, by making the content 16% by mass or less, when the flame-retardant styrene-based resin composition of this embodiment is used as a master batch, excellent dispersibility in the styrene-based resin is exhibited, and the flame retardancy can be improved, and the molded appearance, the flowability of the resin, and the mechanical properties are further improved.
[0033] Generally, styrene-methacrylic acid-based resins including styrene-methacrylic acid-methyl methacrylate copolymer resins, which are one form of the styrene-based copolymer resins in the present invention, are mostly produced by radical polymerization on an industrial scale. However, in this embodiment, in order to suppress the gelling reaction in the devolatilization step, various alcohols can be added to the polymerization system to carry out the polymerization.
[0034] The unsaturated carboxylic acid ester monomer can be used to suppress the dehydration reaction of the unsaturated carboxylic acid monomer through intermolecular interaction with the unsaturated carboxylic acid monomer and to improve the mechanical strength of the resin. Furthermore, the unsaturated carboxylic acid ester monomer also contributes to improving the resin properties such as weather resistance and surface hardness.
[0035] In this embodiment, when the total content of the styrene monomer unit, the unsaturated carboxylic acid monomer unit, and the unsaturated carboxylic acid ester monomer unit is taken as 100% by mass, the content of the unsaturated carboxylic acid ester monomer unit is preferably 0 to 15% by mass, more preferably 1 to 12% by mass, and even more preferably 2 to 10% by mass. By setting the content to 15% by mass or less, the fluidity of the resin can be improved and water absorption can be suppressed. In addition, by setting the lower limit of the content of the unsaturated carboxylic acid ester monomer unit to 0% by mass, the heat resistance can be improved and the cost can be reduced, but from the above viewpoint, the content of the unsaturated carboxylic acid ester monomer unit can also be set to more than 0% by mass.
[0036] In addition, when an unsaturated carboxylic acid monomer and an unsaturated carboxylic acid ester monomer unit are bonded side by side, if a high-temperature, high-vacuum devolatilizer is used, a dealcoholization reaction may occur under certain conditions, resulting in the formation of a six-membered cyclic acid anhydride. The styrene-based copolymer resin of the present embodiment may contain this six-membered cyclic acid anhydride, but since this reduces the fluidity, it is preferable that the amount of the six-membered cyclic acid anhydride produced is as small as possible.
[0037] In the present embodiment, the contents of the styrene-based monomer unit (e.g., styrene monomer unit), the unsaturated carboxylic acid monomer unit (e.g., methacrylic acid monomer unit), and the unsaturated carboxylic acid ester monomer unit (e.g., methyl methacrylate monomer unit) in the styrene-based copolymer resin are respectively measured by proton nuclear magnetic resonance ( 1 It can be calculated from the integral ratio of the spectrum measured by a H-NMR spectrometer.
[0038] In the present embodiment, the styrene-based copolymer resin may further contain monomer units other than the styrene-based monomer units and unsaturated carboxylic acid-based monomer units (e.g., unsaturated carboxylic acid monomer units and unsaturated carboxylic acid ester monomer units), which are examples of other monomers, within a range that does not impair the effects of the present invention. However, the styrene-based copolymer resin in the present invention is preferably typically composed of styrene-based monomer units, unsaturated carboxylic acid monomer units, and / or unsaturated carboxylic acid ester monomer units.
[0039] The styrene-based monomer constituting the styrene-based copolymer resin of the present embodiment is not particularly limited, but examples thereof include styrene, α-methylstyrene, α-methyl-p-methylstyrene, ο-methylstyrene, m-methylstyrene, p-methylstyrene, vinyltoluene, ethylstyrene, isobutylstyrene, t-butylstyrene, bromostyrene, indene and other styrene derivatives. From an industrial viewpoint, styrene is preferred as the styrene-based monomer. These styrene-based monomers can be used alone or in combination of two or more.
[0040] The unsaturated carboxylic acid monomer constituting the styrene-based copolymer resin of this embodiment is not particularly limited, but examples thereof include methacrylic acid, acrylic acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, etc. As the unsaturated carboxylic acid monomer, methacrylic acid is preferred because it has a large effect of improving heat resistance, is liquid at room temperature, and has excellent handling properties. These unsaturated carboxylic acid monomers can be used alone or in combination of two or more.
[0041] The unsaturated carboxylate monomer constituting the styrene copolymer resin of the present embodiment is not particularly limited, but examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and cyclohexyl (meth)acrylate. As the (meth)acrylate monomer, methyl (meth)acrylate is preferred because it has little effect on the decrease in heat resistance. These unsaturated carboxylate monomers may be used alone or in combination of two or more.
[0042] Suitable styrene-based copolymer resins for this embodiment include styrene-methacrylic acid copolymer, styrene-methyl methacrylate copolymer, styrene-methacrylic acid-methyl methacrylate copolymer, styrene-acrylic acid copolymer, styrene-methyl acrylate copolymer, styrene-acrylic acid-methyl acrylate copolymer, styrene-methyl methacrylate-butyl methacrylate copolymer, styrene-butyl methacrylate copolymer, and styrene-maleic anhydride copolymer.
[0043] In this embodiment, the weight average molecular weight (Mw) of the styrene copolymer resin is preferably 100,000 to 350,000, more preferably 120,000 to 300,000, and further preferably 140,000 to 240,000. When the weight average molecular weight (Mw) is 100,000 to 350,000, a resin having a better balance between mechanical strength and fluidity is obtained, and the amount of gel contamination is small. The weight average molecular weight (Mw) is a value obtained by using gel permeation chromatography and converting it into a standard polystyrene equivalent.
[0044] In the present embodiment, the polymerization method for the styrene-based polymer resin is not particularly limited, but for example, a bulk polymerization method or a solution polymerization method can be suitably adopted as a radical polymerization method. The polymerization method mainly includes a polymerization step of polymerizing the polymerization raw materials (monomer components) and a devolatilization step of removing volatile matters such as unreacted monomers and polymerization solvent from the polymerization product.
[0045] Hereinafter, an example of a polymerization method for the styrene-based copolymer resin that can be used in the present embodiment will be described.
[0046] When the polymerization raw materials are polymerized to obtain a styrene-based copolymer resin, a polymerization initiator and a chain transfer agent are typically contained in the polymerization raw material composition.
[0047] Examples of the polymerization initiator used in the polymerization of the styrene-based copolymer resin include organic peroxides, such as peroxyketals such as 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate, dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, and dicumyl peroxide, diacyl peroxides such as acetyl peroxide and isobutyryl peroxide, peroxydicarbonates such as diisopropyl peroxydicarbonate, peroxyesters such as t-butyl peroxyacetate, ketone peroxides such as acetylacetone peroxide, and hydroperoxides such as t-butyl hydroperoxide. Among them, 1,1-bis(t-butylperoxy)cyclohexane is preferred from the viewpoint of decomposition rate and polymerization rate.
[0048] Examples of the chain transfer agent used in the polymerization of the styrene-based copolymer resin include α-methylstyrene linear dimer, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-octyl mercaptan.
[0049] As a polymerization method for the styrene-based copolymer resin, solution polymerization using a polymerization solvent can be adopted as necessary. Examples of the polymerization solvent used include aromatic hydrocarbons, such as ethylbenzene, and dialkyl ketones, such as methyl ethyl ketone, and each of them may be used alone or in combination of two or more. Other polymerization solvents, such as aliphatic hydrocarbons, can be further mixed with aromatic hydrocarbons as long as the solubility of the polymerization product is not reduced. These polymerization solvents are preferably used in an amount not exceeding 25 parts by mass relative to 100 parts by mass of the total monomers. If the amount of the polymerization solvent exceeds 25 parts by mass relative to 100 parts by mass of the total monomers, the polymerization rate is significantly reduced and the mechanical strength of the obtained resin tends to be significantly reduced. It is preferable to add the polymerization solvent at a ratio of 5 to 20 parts by mass relative to 100 parts by mass of the total monomers before polymerization, as this makes it easier to uniformize the quality and is also preferable in terms of polymerization temperature control.
[0050] In this embodiment, the apparatus used in the polymerization step for obtaining a styrene-based copolymer resin is not particularly limited, and may be appropriately selected according to the polymerization method of the styrene-based resin. For example, when bulk polymerization is adopted, a polymerization apparatus having one or more completely mixed reactors connected together can be used. There is also no particular limit to the devolatilization step. When bulk polymerization is adopted, polymerization is continued until the unreacted monomer is preferably 50 mass% or less, more preferably 40 mass% or less, and devolatilization treatment is performed by a known method to remove volatile matters such as the unreacted monomer. More specifically, for example, a normal devolatilization apparatus such as a flash drum, a twin-screw devolatilizer, a thin film evaporator, an extruder, etc. can be used, but a devolatilization apparatus with a small retention portion is preferred. The temperature of the devolatilization treatment is usually about 190 to 280°C, and from the viewpoint of suppressing the formation of a six-membered ring acid anhydride due to the adjacency of an unsaturated carboxylic acid monomer (e.g., methacrylic acid) and an unsaturated carboxylic acid ester monomer (e.g., methyl methacrylate), 190 to 260°C is more preferred. The pressure in the devolatilization treatment is usually about 0.13 to 4.0 kPa, preferably 0.13 to 3.0 kPa, and more preferably 0.13 to 2.0 kPa. Desirable devolatilization methods include, for example, a method of removing volatile matters by reducing pressure under heating, and a method of removing volatile matters through an extruder or the like designed for the purpose of removing volatile matters.
[0051] <Flame retardant (B): (B) component> The flame-retardant styrene-based resin composition of the present embodiment contains 5 to 30 mass% of the flame retardant (B) relative to 100 mass% of the flame-retardant styrene-based resin composition, preferably 8 to 29 mass%, more preferably 10 to 28 mass%, and even more preferably 15 to 25 mass%. In the present embodiment, the content of the phosphinate compound (b) is preferably 70% by mass or more relative to 100% by mass of the total amount of the flame retardant (B). Therefore, the flame retardant (B) may contain 30% by mass or less of a known flame retardant other than the phosphinate compound (b) and / or an optional additive component (such as an antioxidant or an ultraviolet ray inhibitor) described later relative to 100% by mass of the total amount of the flame retardant (B). In the present embodiment, the phosphinate compound (b) is represented by the following general formula (i) and preferably contains at least one phosphinate selected from a phosphinate and a diphosphinate, and more preferably the phosphinate accounts for 70 mass% or more of the entire phosphinate compound (b) (100 mass%). The following general formula (i): [ka] [In the above formula (i), R i1 and R i2 are each independently unsubstituted or one or more hydrogen atoms are substituted by R i3 a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by The substituent R i3 is represented by the following formula (ii): [ka] In the above formula (ii), R ii1 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond to another atom. M i is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and protonated nitrogen base, and p + is M i represents the ionic valence of the compound, is a positive integer of 1 to 3, and m i1 is a positive integer between 1 and 3, and n - represents a negative integer of -1, -2, or -3, r is a positive integer of 1 to 3, |p + ×r|=|n - ×m i1 | Also, R i1 and R ii1 If there are multiple of each, i1 and R ii1may be the same or different.] Therefore, the phosphinate compound (b) in this embodiment may contain a known flame retardant other than the phosphinate represented by general formula (i) in an amount of 30 mass% or less relative to the entire phosphinate compound (b) (100 mass%). In the above formula (i), M i The ionic valence of "p + The absolute value of the product of " and "r" is "n - " and "m i1 " is equal to the absolute value of the product. In (i) above, p + is preferably 1 or 2. i1 is preferably 1 or 2. - is preferably -1 or -2. r is preferably 1 or 2.
[0052] In this embodiment, a preferred phosphinate is represented by the following general formula (1). [ka] [In the above formula (1), R 11 and R 12 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M 1 is at least one selected from the group consisting of calcium ions, magnesium ions, aluminum ions, zinc ions, bismuth ions, manganese ions, sodium ions, potassium ions, and protonated nitrogen bases, + is M 1 represents an ionic valence of 1 to 3, m 1 is an integer between 1 and 3, and a=m 1 R 11 and R 12 If there are multiple of each, 11 and R 12 may be the same or different.]
[0053] In this embodiment, a preferred diphosphinate is represented by the following general formula (2). [ka] [In the above formula (2), R 21 and R 22 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; L 23 is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 14 carbon atoms, or an arylalkylene group having 6 to 14 carbon atoms; M 2 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and protonated nitrogen bases, and b + is M 2 represents an ionic valence of 1 to 3, m 2 is an integer from 1 to 3, q is an integer of 1 or 2, and b×q=2m 2 R 21 and R 12 If there are multiple of each, 21 and R 22 may be the same or different.
[0054] In the above formulas (i), (ii), (1) and (2), examples of the linear or branched alkyl group having 1 to 6 carbon atoms include linear alkyl groups such as a methyl group, an ethyl group, a propyl group, a butyl group, an amyl group or a hexyl group, and branched alkyl groups such as an isopropyl group, an isobutyl group, a s-butyl group, a t-butyl group, an isoamyl group or a t-amyl group. In the above formulae (i), (ii), (1) and (2), the aryl group having 6 to 10 carbon atoms may have a monocyclic or condensed ring structure, for example, a phenyl group or a naphthyl group. In the above formula (2), examples of the linear or branched alkylene group having 1 to 10 carbon atoms include groups in which one hydrogen atom has been removed from the above linear or branched alkyl group having 1 to 6 carbon atoms. In the above formula (2), examples of the arylene group having 6 to 10 carbon atoms include groups in which one hydrogen atom has been removed from the above aryl group having 6 to 10 carbon atoms. In the above formula (i), examples of the aralkyl group having 6 to 14 carbon atoms include a benzyl group, a phenylethyl group, a phenylpropyl group, a phenylbutyl group, a methylphenyl group, an ethylphenyl group, a propylphenyl group, a butylphenyl group, a methylnaphthyl group, an ethylnaphthyl group, and a tert-butylnaphthyl group. In the above formula (2), examples of the alkylarylene group having 6 to 14 carbon atoms include a methylphenylene group, an ethylphenylene group, a tert-butylphenylene group, a methylnaphthylene group, an ethylnaphthylene group, and a tert-butylnaphthylene group. In the above formula (2), examples of the arylalkylene group having 6 to 14 carbon atoms include a phenylmethylene group, a phenylethylene group, a phenylpropylene group, and a phenylbutylene group. In the above formula (1), R 11 and R 12 is preferably each independently a linear alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. In the above formula (1), M 1 is preferably calcium, magnesium, aluminum, or zinc. 1 represents the ionic valence, which is 2 or 3. In the above formula (2), R 21 and R 22 is preferably each independently a linear alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms. In the above formula (2), L 23 are each preferably independently a linear alkylene group having 1 to 6 carbon atoms or an arylene group having 6 to 10 carbon atoms. In the above formula (2), M 2is preferably calcium, magnesium, aluminum, or zinc. 2 represents the ionic valence, which is 2 or 3. The phosphinic acid salt compound (b) has excellent electrical properties, making it suitable for flame-retardant materials that require insulation. It also has excellent hydrolysis properties, making it suitable for use in applications under high temperature and high humidity conditions, and it also has excellent recyclability.
[0055] The phosphinic acid salt (b) used in the present embodiment is produced in an aqueous solution using, inter alia, phosphinic acid and a metal carbonate, metal hydroxide or metal oxide, and is essentially a monomeric compound, but also includes polymeric phosphinic acid salts with a degree of condensation of 1 to 3 under certain circumstances, depending on the reaction conditions.
[0056] Such phosphinate (b) is not particularly limited, and examples thereof include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methane di(methylphosphinate), magnesium methane di(methylphosphinate), aluminum methane di(methylphosphinate), zinc methane di(methylphosphinate), calcium benzene-1,4-(dimethylphosphinate), benzene-1,4 -(dimethylphosphinate)magnesium, benzene-1,4-(dimethylphosphinate)aluminum, benzene-1,4-(dimethylphosphinate)zinc, calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate are preferred, including calcium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, aluminum ethylmethylphosphinate, aluminum ethylbutylphosphinate, aluminum dibutylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, aluminum diethylphosphinate, and zinc diethylphosphinate, with aluminum diethylphosphinate being more preferred. Commercially available phosphinate compounds (b) are not particularly limited, and examples thereof include Exolit (registered trademark) OP1230, OP1240, OP1311, OP1312, OP930, and OP935 manufactured by Clariant Japan K.K.
[0057] In this embodiment, the phosphinate compound (b) is preferably granular. When the phosphinate compound (b) is granular, the average particle size of the phosphinate compound (b) is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 20 μm or less, from the viewpoint of improving the mechanical strength and appearance of the molded article obtained by molding the flame-retardant resin composition of this embodiment, and it is preferable to use a powder of the phosphinate compound (b) pulverized to this particle size. It is preferably more than 0.5 μm and 20 μm, more preferably more than 1 μm and 20 μm or less. When a powder with a preferred particle size is used, not only high flame retardancy is exhibited, but also impact strength is remarkably increased, which is particularly preferable. The average particle size of the granular phosphinate compound (b) is measured based on the volumetric particle size measured using a laser diffraction / scattering particle size distribution analyzer. The value is measured using a 3% isopropanol aqueous solution as the dispersion medium of the phosphinate compound (b). Specifically, the average particle size can be obtained by using a laser diffraction / scattering particle size distribution analyzer LA-910 (manufactured by Horiba, Ltd.) to perform a blank measurement using a dispersion medium of 3% isopropanol aqueous solution, and then putting the measurement sample so that the transmittance is set to the specified value (95% to 70%). The sample is dispersed in the dispersion medium by irradiating it with ultrasonic waves for 1 minute.
[0058] <Cellulosic polysaccharides (C) (hereinafter also referred to as component (C))> The content of the cellulose polysaccharides (C) in this embodiment is 3 to 30% by mass, preferably 5 to 28% by mass, and more preferably 10 to 25% by mass, based on 100% by mass of the flame-retardant styrene-based resin composition. By making the content of the cellulose polysaccharides (C) 3% by mass or more, it is possible to improve low smoke generation, flame retardancy, and dimensional accuracy. On the other hand, if the content is too much more than 30% by mass, the flame retardancy decreases and the moldability is significantly reduced due to the decrease in fluidity. The content of the cellulose polysaccharides (C) in the composition can be found by dissolving the composition in a solvent that dissolves the styrene-based resin, removing the undissolved matter, and measuring the mass of the product dried at 120°C for 4 hours.
[0059] The shape of the cellulose polysaccharide (C) in this embodiment is not particularly limited, and examples thereof include spherical, irregular, powdery, scaly, fibrous, and rod-like shapes. At least one of the average lengths of the minor axis d1 and major axis d2 of the cellulose polysaccharide (C) is 10 to 80 μm, preferably 15 to 70 μm, preferably 20 to 60 μm, and more preferably 30 to 50 μm. If the average lengths of the minor axis d1 and major axis d2 are outside the above range, the dimensional accuracy may not be fully exhibited, or the anisotropy may become large in the MD and TD directions. On the other hand, if the average lengths of the minor axis d1 and major axis d2 are within the above range, the aggregation of the cellulose polysaccharide (C) can be reduced, and the dispersibility in the styrene resin (A) is improved, thereby improving the oil resistance and moldability. In the cellulose polysaccharide (C) of this embodiment, the average length of the minor axis d1 is preferably equal to or less than the average length of the major axis d2, and the average length of the minor axis d1 is preferably less than the average length of the major axis d2. In the present invention, the average length of the minor axis d1 of the cellulose polysaccharide (C) is obtained by measuring the minor axis length (minimum length) of 100 cellulose polysaccharides (C) by transmission electron microscope observation (magnification of 5000 times) and taking the arithmetic average. On the other hand, the average length of the major axis of the cellulose polysaccharide (C) is obtained by measuring the major axis length (maximum length) of 100 cellulose polysaccharides (C) by transmission electron microscope observation (magnification of 5000 times) and taking the arithmetic average. In addition, the average length of the minor axis of the cellulose polysaccharide (C) is obtained by measuring the minor axis length (minimum length) of the cellulose polysaccharide (C) and using the same method as the average length of the major axis. The short axis length (minimum length) of the cellulose polysaccharide (C) refers to the length of the thinnest (or shortest) point on the image, and the long axis length (maximum length) of the cellulose polysaccharide (C) refers to the length of the longest point on the image. Linear expansion is affected by the shape of the cellulose polysaccharide (C), and in the case of fibers, it is affected by the short axis, while in the case of scale-like or granular, it is affected by the average diameter of the long axis. The aspect ratio (d1 / d2) of the average length of the minor axis d1 to the average length of the major axis d2 of the cellulose polysaccharide (C) in the present invention is preferably 1 to 500, more preferably 1.2 to 300, even more preferably 1.5 to 200, and particularly preferably 2 to 100.
[0060] The cellulose polysaccharide (C) in the present invention refers to a polysaccharide having a β-1,4-glucan structure, and includes cellulose and hemicellulose. The material of the cellulose polysaccharide (C) is not particularly limited as long as the fibers constituting the cellulose polysaccharide (C) are formed of polysaccharides having a β-1,4-glucan structure, and may be, for example, cellulose fibers derived from higher plants [e.g., natural cellulose fibers (pulp fibers) such as wood fibers (wood pulp of coniferous trees, broad-leaved trees, etc.), bamboo fibers, sugarcane fibers, seed hair fibers (cotton linters, bombax cotton, kapok, etc.), ginseng bark fibers (e.g., hemp, paper mulberry, mitsumata, etc.), and leaf fibers (e.g., Manila hemp, New Zealand hemp, etc.), animal-derived cellulose fibers (sea squirt cellulose, etc.), bacterial-derived cellulose fibers, and chemically synthesized cellulose fibers [cellulose acetate (acetic acid) Examples of the fibers constituting the cellulose polysaccharide (C) include organic acid esters such as cellulose nitrate, cellulose sulfate, cellulose phosphate, etc.; mixed acid esters such as cellulose acetate nitrate, etc.; hydroxyalkyl celluloses (e.g., hydroxyethyl cellulose (HEC), hydroxypropyl cellulose, etc.); carboxyalkyl celluloses (carboxymethyl cellulose (CMC), carboxyethyl cellulose, etc.); alkyl celluloses (methyl cellulose, ethyl cellulose, etc.); and cellulose derivative fibers such as regenerated cellulose (rayon, cellophane, etc.). These fibers constituting the cellulose polysaccharide (C) may be used alone or in combination of two or more.
[0061] Among the fibers constituting the above-mentioned cellulose polysaccharide (C), preferred are plant-derived cellulose fibers, for example, cellulose fibers derived from pulp such as wood fibers (wood pulp of coniferous trees, broad-leaved trees, bamboo, etc.) and seed hair fibers (cotton linter pulp, etc.), because they have high production efficiency in terms of dispersibility, rigidity, and impact resistance when producing the cellulose polysaccharide (C) and have appropriate fiber diameter and fiber length. In this embodiment, the lignin content in 100% by mass of the cellulose polysaccharide (C) is preferably 20% by mass or less, and more preferably 10% by mass or less. If the lignin content in the cellulose polysaccharide (C) is more than 20% by mass, odor and coloring will increase during thermal processing, and lignin degradation products will turn into charcoal-like black spots, reducing the product value, and causing problems with white coloring. Furthermore, in this embodiment, it is preferable that hemicellulose is contained in an amount of 1% by mass or more relative to 100% by mass of the cellulose polysaccharide (C). By containing hemicellulose, dispersibility with the styrene resin (A) is improved, and rigidity and molded appearance can be improved. In the present invention, it is preferable that these components are not completely removed in the manufacturing process of the cellulose polysaccharide (C) but are allowed to remain in a content within a suitable range. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in connecting microfibrils by hydrogen bonding with cellulose. In addition, since the solubility parameter (SP value) of hemicellulose is on the hydrophobic side compared to cellulose, it is considered that hemicellulose has an effect of reducing the SP value difference between the styrene resin (A) and the cellulose polysaccharide (C). In addition, by containing 1% or more of hemicellulose, the air bubble diameter is reduced, and the compressive strength and heat resistance are improved. The amount of hemicellulose in the cellulosic polysaccharide (C) can be adjusted to a desired amount by subjecting natural wood raw materials with a high hemicellulose content to a purification treatment. For example, when a raw material with a low hemicellulose content is used, the amount can be adjusted to a desired amount by adding hemicellulose obtained by extraction treatment from another raw material. In this case, it does not matter if the structure of the terminals of the hemicellulose, etc., is partially different from that of the natural product due to the purification or extraction treatment. In this embodiment, for the purpose of reducing the SP value difference between the styrene-based resin (A) and the cellulose-based polysaccharide (C), it is more preferable that hemicellulose is contained in the cellulose-based polysaccharide (C) (100 mass%) in an amount of 1 mass% or more and 25 mass% or less, even more preferable that it is contained in an amount of 2 mass% or more and 20 mass% or less, even more preferable that it is contained in an amount of 3 mass% or more and 20 mass% or less, even more preferable that it is contained in an amount of 5 mass% or more and 19.5 mass% or less, and especially preferable that it is contained in an amount of 7 mass% or more and 19.3 mass% or less.
[0062] <Dispersant> In this embodiment, a dispersant may be contained in the styrene resin composition or the styrene resin molded product in order to improve the dispersibility of the flame retardant (B) and the cellulose polysaccharide (C). The dispersant may be added in an amount of 0.5 to 20 parts by weight per 100 parts by weight of the total of the (A) component, the (B) component, and the (C) component. By adding the dispersant, it is possible to prevent scorching and eye discharge of the extruder when the flame retardant (B) and the cellulose polysaccharide (C) are compounded with the styrene resin (A), and to improve the appearance of the molded product. If the amount of the dispersant is less than the specified amount, such an effect is not obtained, and if the amount is more than the specified amount, the heat resistance is reduced. The effect is greater if the dispersant has excellent affinity with the styrene resin (A).
[0063] The dispersant may be a fatty acid ester compound, a polyethylene glycol compound, a terpene compound, a rosin compound, a fatty acid amide, a fatty acid, a fatty acid metal salt, etc. In particular, fatty acid ester compounds, polyethylene glycol compounds, terpene compounds, and rosin compounds are preferred. Examples of aliphatic ester lubricants include methyl laurate, methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl erucate, methyl behenate, butyl laurate, butyl stearate, isopropyl myristate, isopropyl palmitate, octyl palmitate, coconut fatty acid octyl ester, octyl stearate, tallow fatty acid octyl ester, lauryl laurate, stearyl stearate, behenyl behenate, cetyl myristate, esters of linear, unbranched, saturated monocarboxylic acids having 28 to 30 carbon atoms (hereinafter abbreviated as montanic acid) and ethylene glycol, esters of montanic acid and glycerin, and montanic acid. Examples of the esters include esters of montanic acid and butylene glycol, esters of montanic acid and trimethylolethane, esters of montanic acid and trimethylolpropane, esters of montanic acid and pentaerythritol, glycerin monostearate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, etc. These may be used in combination of two or more kinds.
[0064] The terpene resin is generally obtained by copolymerizing a terpene monomer alone, or a terpene monomer and an aromatic monomer, or a terpene monomer and a phenol in an organic solvent in the presence of a Friedel-Crafts catalyst, but is not limited thereto. Alternatively, the terpene resin may be a hydrogenated terpene resin obtained by subjecting the obtained terpene resin to a hydrogenation treatment. Examples of the terpene resin include α-pinene resin, β-pinene resin, aromatic modified terpene resin, terpene phenol resin, and hydrogenated terpene resin. Examples of the terpene monomer include, but are not limited to, hemiterpenes having 5 carbon atoms such as isoprene, α-pinene, β-pinene, dipentene, d-limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, γ-terpineol, sabinene, paramentadienes, and carenes, monoterpenes having 10 carbon atoms such as caryophyllene and longifolene, and diterpenes having 20 carbon atoms. Among these compounds, α-pinene, β-pinene, dipentene, and d-limonene are particularly preferably used. Examples of aromatic monomers include, but are not limited to, styrene, α-methylstyrene, vinyltoluene, isopropenyltoluene, etc. Examples of phenols include, but are not limited to, phenol, cresol, xylenol, bisphenol A, etc.
[0065] Examples of rosin-based resins include rosins such as gum rosin, wood rosin, and tall oil rosin, as well as stabilized rosins obtained by disproportionating or hydrogenating the above-mentioned rosins, polymerized rosins (typically dimers) which are polymers of the above-mentioned rosins, and modified rosins modified with unsaturated acids such as maleic acid, fumaric acid, and (meth)acrylic acid. Examples of rosin derivative resins include esters of the above-mentioned rosin-based resins, phenol-modified products, and esters thereof. The rosin-based resins or rosin derivative resins used in the present invention are not limited to these resins.
[0066] Examples of the aliphatic amide lubricants include stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, ethylene bisstearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, and ethylene bislauric acid amide. These may be used in combination of two or more kinds.
[0067] Specific examples of saturated fatty acids among fatty acids include lauric acid (dodecanoic acid), isodecanoic acid, tridecyl acid, myristic acid (tetradecanoic acid), pentadecylic acid, palmitic acid (hexadecanoic acid), margaric acid (heptadecanoic acid), stearic acid (octadecanoic acid), isostearic acid, tuberculostearic acid (nonadecanoic acid), 2-hydroxystearic acid, arachidic acid (icosanoic acid), behenic acid (docosanoic acid), lignoceric acid (tetradocosanoic acid), cerotic acid (hexadocosanoic acid), montanic acid (octadocosanoic acid), and melissic acid, and in particular, lauric acid, palmitic acid, stearic acid, behenic acid, 12-hydroxystearic acid, and montanic acid.
[0068] Specific examples of unsaturated fatty acids among fatty acids include myristoleic acid (tetradecenoic acid), palmitoleic acid (hexadecenoic acid), oleic acid (cis-9-octadecenoic acid), elaidic acid (trans-9-octadecenoic acid), ricinoleic acid (octadecadienoic acid), vaccenic acid (cis-11-octadecenoic acid), linoleic acid (octadecadienoic acid), linolenic acid (9,11,13-octadecatrienoic acid), elestearic acid (9,11,13-octadecatrienoic acid), gadoleic acid (icosanoic acid), erucic acid (docosanoic acid), nervonic acid (tetradocosanoic acid), etc. These may be used in combination of two or more kinds.
[0069] Examples of the fatty acid metal salt lubricant include lithium salts, calcium salts, magnesium salts, zinc salts, and aluminum salts of the fatty acids of the above fatty acid lubricants. These may be used in combination of two or more kinds.
[0070] <Optional addition ingredients> In this embodiment, the flame-retardant styrene-based resin composition may contain optional components such as conventionally known additives, processing aids, etc., in addition to the above-mentioned components (A) to (C), as necessary, within the scope of not impairing the effects of the present invention. Examples of these optional components include antioxidants, weathering agents, antistatic agents, fillers, etc.
[0071] Examples of the antioxidant include phenol-based compounds, phosphorus-based compounds, and thioether-based compounds.
[0072] Examples of the phenol-based antioxidant include 2,6-di-t-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl (3,5-di-t-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-t-butyl-4-hydroxyphenyl)propionic acid amide], 4,4'-thiobis(6-t-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4, 4'-butylidenebis(6-t-butyl-m-cresol), 2,2'-ethylidenebis(4,6-di-t-butylphenol), 2,2'-ethylidenebis(4-tert-butyl-6-t-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-t-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, hydroxybenzyl)-2,4,6-trimethylbenzene, 2-t-butyl-4-methyl-6-(2-acryloyloxy-3-t-butyl-5-methylbenzyl)phenol, stearyl [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], tetrakis [methyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, thiodiethylene glycol bis[(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylene bis[(3,5-di-t-butyl-4-hydroxyphenyl)propionate] oxyphenyl)propionate], bis[3,3-bis(4-hydroxy-3-t-butylphenyl)butyric acid] glycol ester, bis[2-t-butyl-4-methyl-6-(2-hydroxy-3-t-butyl-5-methylbenzyl)phenyl] terephthalate, 1,3,5-tris[(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxyethyl] isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,Examples include 10-tetraoxaspiro[5,5]undecane, triethylene glycol bis[(3-t-butyl-4-hydroxy-5-methylphenyl)propionate], etc. These may be used alone or in combination of two or more.
[0073] Examples of the phosphorus-based antioxidant include tris(2,4-di-t-butylphenyl)phosphite, trisnonylphenyl phosphite, tris[2-t-butyl-4-(3-t-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, and the like. ritol diphosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tri-t-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4' -n-butylidenebis(2-t-butyl-5-methylphenol)diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butanetriphosphite, tetrakis(2,4-di-t-butylphenyl)biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-t-butylphenyl)-2-ethylhexylphosphite phosphite, 2,2'-methylenebis(4,6-t-butylphenyl)-octadecylphosphite, 2,2'-ethylidenebis(4,6-di-t-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-t-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, and phosphite of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-t-butylphenol. These may be used alone or in combination of two or more.
[0074] Examples of the thioether antioxidant include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and pentaerythritol tetra(β-alkylmercaptopropionate esters). These may be used alone or in combination of two or more.
[0075] As the weather resistance agent, an ultraviolet absorber, a hindered amine light stabilizer, etc. can be used. Examples of the ultraviolet absorber include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, and the like. 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-t-octyl-6-(benzotriazolyl)phenol), and 2-(2'-hydroxy-3'-t-butyl-5'-carboxyphenyl)benzotriazole; phenyl salicylate Benzoates such as 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, 2,4-di-t-amylphenyl-3,5-di-t-butyl-4-hydroxybenzoate, and hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide and 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl cyanoacrylates such as aryl-2-cyano-3-methyl-3-(p-methoxyphenyl)acrylate; and triaryltriazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-t-butylphenyl)-s-triazine. These may be used alone or in combination of two or more.
[0076] Examples of the hindered amine-based light stabilizer include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1 ,2,3,4-butane tetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butane tetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butane tetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-di-t-butyl-4-butyl) hydroxybenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-t-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl 1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,Examples of the hindered amine compounds include 2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl)aminoundecane. These may be used alone or in combination of two or more.
[0077] As the antistatic agent, cationic, anionic, nonionic, amphoteric, fatty acid partial esters such as glycerin fatty acid monoesters, and the like can be used. Specifically, alkyl trimethyl ammonium salts, dialkyl dimethyl ammonium salts, benzalkonium salts, N,N-bis(2-hydroxyethyl)-N-(3-dodecyloxy-2-hydroxypropyl)methyl ammonium methosulfate, (3-lauryl amidopropyl)trimethyl ammonium methyl sulfate, stearamidopropyl dimethyl-2-hydroxyethyl ammonium nitrate, stearamidopropyl dimethyl-2-hydroxyethyl ammonium phosphate, cationic polymers, alkyl sulfonates, alkyl benzene sulfonates, sodium alkyl diphenyl ether disulfonate, alkyl nitrate ester salts, phosphorus Acid alkyl ester salts, alkyl phosphate amine salts, stearic acid monoglyceride, pentaerythritol fatty acid esters, sorbitan monopalmitate, sorbitan monostearate, diglycerin fatty acid esters, alkyldiethanolamines, alkyldiethanolamine fatty acid monoesters, alkyldiethanolamides, polyoxyethylene dodecyl ethers, polyoxyethylene alkylphenyl ethers, polyethylene glycol monolaurates, polyoxyethylene alkylamines, polyoxyethylene alkylamides, polyether block copolymers, cetyl betaine, and hydroxyethyl imidazoline sulfate. These may be used alone or in combination of two or more.
[0078] As the filler, talc, calcium carbonate, barium sulfate, carbon fiber, mica, wollastonite, whisker, etc. can be used.
[0079] In this embodiment, the flame-retardant styrene-based resin composition may contain, in addition to the above-mentioned optional additive components, optional additive components such as an antiblocking agent, a colorant, an antiblooming agent, a surface treatment agent, an antibacterial agent, and an anti-viscosity agent (anti-viscosity agents such as the silicone oil described in JP 2009-120717 A, monoamide compounds of higher aliphatic carboxylic acids, and monoester compounds obtained by reacting higher aliphatic carboxylic acids with monohydric to trihydric alcohol compounds). In this embodiment, the total content of the above-mentioned optional additive components may be 0.05 to 5% by mass in the flame-retardant styrene-based resin composition.
[0080] The flame-retardant styrene-based resin composition of the present embodiment may consist essentially of only the components (A), (B), and (C).Also, the flame-retardant styrene-based resin composition may consist essentially of only the components (A), (B), (C), a dispersant, and optional additive components. The phrase "consisting essentially of only the components (A), (B), and (C)" means that the components (A), (B), and (C) account for 80 to 100 mass% (preferably 88 to 100 mass%) of the total amount (100 mass%) of the flame-retardant styrene-based resin composition. The phrase "consisting essentially of only the components (A), (B), (C), the dispersant, and any optional additional components" means that the components (A), (B), (C), the dispersant, and any optional additional components account for 95 to 100 mass% (preferably 98 to 100 mass%) of the total amount (100 mass%) of the flame-retardant styrene-based resin composition. The flame-retardant styrene-based resin composition of the present embodiment may contain inevitable impurities in addition to the components (A), (B), and (C), the dispersant, and any optional additional components, as long as the effects of the present invention are not impaired.
[0081] The flame-retardant styrene resin composition of the present embodiment contains a styrene resin (A), a phosphinate compound (b), a cellulose polysaccharide (C) having at least one of the average lengths of the minor axis d1 and the major axis d2 of 10 to 80 μm, and a dispersant and / or optional additional components added as needed, in a predetermined amount. The materials or properties of the styrene resin (A), the phosphinate compound (b), the cellulose polysaccharide (C), and the dispersant and / or optional additional components added as needed, which are added to the styrene resin composition, are as described above. The amounts of the (A) component, the (B) component, the (C) component, the dispersant, and the optional additional components added can be appropriately adjusted and added so that the content in the flame-retardant styrene resin composition falls within the above range.
[0082] <Method for producing flame-retardant styrene-based resin composition> The flame-retardant styrene-based resin composition of the present embodiment can be produced by melt-kneading each component by any method. For example, a high-speed stirrer such as a Henschel mixer, a batch-type kneader such as a Banbury mixer, a single-screw or twin-screw continuous kneader, a roll mixer, etc. can be used alone or in combination. The heating temperature during kneading is usually selected in the range of 180 to 260°C.
[0083] [Physical properties of flame-retardant styrene-based resin composition] <Flame retardancy> The flame retardancy of the flame-retardant styrene-based resin composition of the present embodiment is preferably within the standard in the UL94 vertical flame test (UL94-V test), i.e., flame retardancy class of V-0 to V-2. It is also preferable that the composition does not generate black smoke during combustion. In the present disclosure, flame retardancy and black smoke can be evaluated by the method described in the section [Examples] below.
[0084] <Linear expansion coefficient> The linear expansion coefficient of the molded body obtained from the flame-retardant styrene-based resin composition of this embodiment is 6.5 × 10 -5 / °C or less, and more preferably 5×10 -5 / ° C. or less. The ratio of the linear expansion coefficient in the MD direction (flow direction during molding) to the TD direction (direction perpendicular to the MD direction) (TD / MD ratio) is preferably 0.8 to 1.2, and more preferably 0.9 to 1.1. The linear expansion coefficient is 6×10 -5 If the TD / MD ratio is greater than 1 / °C, the thermal expansion may cause defects in the product, or the metal may peel off in products that are bonded to metals. If the TD / MD ratio is outside the range, the product may warp due to heat. In this disclosure, the linear expansion coefficient is a value measured in accordance with the TMA method of JIS K7197. The dimensional accuracy of the molded product produced using the flame-retardant styrene-based resin composition of this embodiment is evaluated by the value of the linear expansion coefficient.
[0085] <Yellow Index> The yellow index of the flame-retardant styrene-based resin composition of the present embodiment is preferably equal to or less than 20, and more preferably equal to or less than 15. If it is greater than 20, coloring may become difficult.
[0086] [Molded products] The flame-retardant styrene-based resin composition of the present embodiment can be used to produce a molded article by the above-mentioned melt kneading molding machine, or by using pellets of the obtained flame-retardant styrene-based resin composition as a raw material, through injection molding, injection compression molding, extrusion molding, blow molding, press molding, vacuum molding, foam molding, or the like.
[0087] The flame-retardant styrene-based resin composition of the present embodiment is preferably used for molded articles, preferably injection molded articles (including injection compression), office automation equipment such as copiers, fax machines, televisions, radios, tape recorders, video decks, personal computers, printers, telephones, information terminals, refrigerators, and microwave ovens, home appliances, housings and various parts of electric and electronic devices, foamed insulation materials, insulating films, and the like. EXAMPLES
[0088] Hereinafter, the embodiments of the present invention will be described in more detail based on examples and comparative examples, but the present invention is not limited to these examples in any way. <Measurement and evaluation methods> The physical properties of the resin compositions obtained in each of the Examples and Comparative Examples were measured and evaluated according to the following methods. (1) Flame retardancy evaluation (i) Burning class rating and burning time rating Using a test piece (b) (size: 127 mm × 12.7 mm, thickness: 1.5 mm) prepared by the method described below, flame retardancy was evaluated according to a method conforming to the UL94 vertical flame test (UL94-V test) using a test flame of 50 W. The flame of a gas burner was applied to the test piece (b) to evaluate the degree of combustion. The flame retardancy grade indicates the flame retardancy class as classified by the UL94-V test. The test was performed on five pieces for each test piece and the judgment was made. The classification method is as follows: V-0: Total burning time of 5 sticks is 50 seconds or less, maximum burning time is 10 seconds or less, no cotton dripping ignition V-1: Total burn time of 5 sticks is 250 seconds or less, maximum burn time is 30 seconds or less, no cotton dripping ignition V-2: Total burn time of 5 sticks is 250 seconds or less, maximum burn time is 30 seconds or less, cotton dripping may ignite Not V: Not compliant with UL94 In addition, the generation of black smoke during combustion was judged by visual inspection. If black smoke was generated during combustion, it was rated as ×, if only a small amount was generated, it was rated as △, and if almost no smoke was generated, it was rated as ◯.
[0089] (2) Linear expansion coefficient The linear expansion coefficient ( / °C) was measured in the MD and TD directions by cutting the center of the test piece (a) prepared by the method described below into a size of 10 × 5 × 4 mm in the MD and TD directions according to the TMA method (-30°C to 80°C) of JIS K7197.
[0090] (3) Yellow Index For the test piece (a) prepared by the method described below, the yellow index of the resin composition was measured in accordance with JIS K7105 using a color difference turbidity meter COH300A (product name) manufactured by Nippon Denshoku Co., Ltd. Taking into account the purpose of color matching, a value of 5 or less was considered acceptable.
[0091] (4) Contents of styrene monomer units, methacrylic acid monomer units, and methyl methacrylate monomer units in the styrene-based resin (a) Proton nuclear magnetic resonance ( 1 The resin composition was quantified from the integral ratio of the spectrum measured by a 1 H-NMR measuring device. Sample preparation: 30 mg of resin pellets were dissolved in 0.75 mL of d6-DMSO by heating at 60°C for 4 to 6 hours. ·Measuring equipment: JNM ECA-500 manufactured by JEOL Ltd. Measurement conditions: Measurement temperature 25℃, observation nucleus 1 H, accumulation count 64, repeat time 11 seconds.
[0092] (Spectral assignment) Regarding the assignment of the spectrum measured in dimethyl sulfoxide deuterated solvent, the peaks at 0.5 to 1.5 ppm are peaks derived from hydrogen of α-methyl group of methacrylic acid, methyl methacrylate, and six-membered cyclic acid anhydride, the peaks at 1.6 to 2.1 ppm are peaks derived from hydrogen of methylene group of polymer main chain, the peak at 3.5 ppm is peak derived from hydrogen of carboxylate ester (-COOCH3) of methyl methacrylate, and the peak at 12.4 ppm is peak derived from hydrogen of carboxylate of methacrylic acid. In addition, the peaks at 6.5 to 7.5 ppm are peaks derived from hydrogen of aromatic ring of styrene. Note that the content of six-membered cyclic acid anhydride is small in the resins of the present embodiment and the comparative example, so that quantification is usually difficult by this measurement method.
[0093] (5) Measurement of the average length of cellulosic polysaccharides From the pellets obtained from the kneaded product, ultrathin slices with a thickness of 75 nm were prepared, and photographs were taken at a magnification of 50,000 times using an electron microscope. The photographs were then scanned at a resolution of 200 dpi, and the minimum and maximum lengths of 100 cellulose polysaccharides (C) were measured using particle analysis software of an image analyzer IP-1000 (manufactured by Asahi Kasei Corporation), and the arithmetic averages were taken as the average length d1 of the minor axis and the average length d2 of the major axis. Similarly to the above, a photograph of the cellulose polysaccharide (C) alone was taken at a magnification of 50,000 times using an electron microscope, and the arithmetic averages were taken as the average length d1 of the minor axis and the average length d2 of the major axis.
[0094] (6) Quantification of lignin content The quantitative analysis of lignin in cellulosic polysaccharides (C) was performed based on the TGA method described in the Journal of the Japan Society of Material Cycles and Waste Management, Vol. 22, No. 5, p. 293, 2011. The thermogravimetric analyzer used was a Shimadzu Corporation DTG-60 model, and the temperature was raised from room temperature to 900°C at a heating rate of 10°C / min in an air atmosphere. The samples to be analyzed were dried at 70°C for 2 hours, and 3-5 mg were precisely weighed out to measure the weight change due to thermal decomposition. The sample container used was a disc-shaped platinum dish with an inner diameter of 5 mm and a height of 2 mm, and all experiments were performed under fixed conditions.
[0095] (7) Measurement of hemicellulose content Quantitative analysis of hemicellulose in cellulosic polysaccharides (C) is as follows. The dispersion medium was removed from the dispersion of the cellulose polysaccharide (C) or from a redispersion of the cellulose polysaccharide (C) obtained by dissolving and removing the resin component from the styrene-based resin composition, and the cellulose residue was recovered and dried at 105°C to obtain a dry sample, and the mass of the dry sample was measured by the following method. The dried cellulose residue was ground to obtain a ground sample, which was extracted with an alcohol (ethanol) / benzene mixed solvent in a Soxhlet extractor for 6 hours. Then, extraction was performed for another 4 hours with an alcohol (ethanol) / benzene mixed solvent to obtain a defatted sample. 150 mL of distilled water, 1.0 g of sodium chlorite, and 0.2 mL of acetic acid were added to 2.5 g of the defatted sample, and the mixture was heated at 70-80°C for 1 hour. Then, 1.0 g of sodium chlorite and 0.2 mL of acetic acid were added again, and the mixture was heated at 70-80°C for 1 hour. This operation was repeated 3-4 times until the sample was decolorized to white. The obtained sample was filtered, washed with water and acetone, and dried at 105°C to obtain a holocellulose fraction (the total amount of α-cellulose and hemicellulose). The mass of this holocellulose fraction was measured. Next, 25 mL of 17.5% by mass sodium hydroxide aqueous solution was added to 1.0 g of the holocellulose fraction, and after 3 minutes, the mixture was lightly crushed with a glass rod until it became swollen. After that, the mixture was left to stand at 20°C, and 30 minutes after the addition of the sodium hydroxide aqueous solution, 25 mL of distilled water was added, stirred for exactly 1 minute, left to stand at 20°C for 5 minutes, filtered through a glass filter, and washed until the filtrate became neutral. Further, 40 mL of 10% by mass acetic acid was suction filtered, and then 1 L of boiling water was suction filtered and the washed sample was dried at 105°C until the mass became constant, to obtain an α-cellulose fraction. The mass of this α-cellulose fraction was measured. The hemicellulose content was calculated from the masses of the holocellulose fraction and the α-cellulose fraction determined as above using the following formula. Holocellulose (%) = holocellulose fraction (g) / sample (anhydrous basis) (g) x 100 α-Cellulose (%) = α-Cellulose fraction (g) / sample (anhydrous basis) (g) × 100 Hemicellulose (%) = Holocellulose (%) - (α-cellulose (%))
[0096] (8) Method for measuring the average particle size of the phosphinate compound (b) The method for measuring the average particle size of the granular phosphinate compound (b) is based on the volume-based particle size measured using a laser diffraction / scattering type particle size distribution measuring device. The value is measured using a 3% isopropanol aqueous solution as the dispersion medium of the phosphinate compound (b). Specifically, a laser diffraction / scattering type particle size distribution measuring device LA-910 (manufactured by Horiba, Ltd.) was used to perform a blank measurement using a 3% isopropanol aqueous solution as the dispersion medium, and then the measurement sample was placed so that the transmittance was the specified value (95% to 70%) and measured. The sample was dispersed in the dispersion medium by irradiating it with ultrasonic waves for 1 minute.
[0097] The materials used in the examples and comparative examples are as follows. [Styrene-based resin (A)] [GPPS-1] Polystyrene with MFR 7.8 (GPPS, PS Japan, HF77) was used. [HIPS-1] A rubber-modified polystyrene resin with MFR 3.0 (HIPS, manufactured by PS Japan, HT478) was used.
[0098] [Copolymer resin-1] A polymerization raw material composition liquid consisting of 70.0 parts by mass of styrene (ST), 15.0 parts by mass of butyl methacrylate (BA), 15.0 parts by mass of ethylbenzene, and 0.025 parts by mass of 1,1-bis(t-butylperoxy)cyclohexane was continuously fed at a rate of 1.1 L / hour to a 4-L complete mixing reactor, then to a polymerization apparatus consisting of a 2-L laminar flow reactor, and further to a devolatilizer connected to a single-screw extruder for removing volatile matters such as unreacted monomers and polymerization solvent, to prepare copolymer resin-1, which is a styrene-based copolymer resin. The polymerization reaction conditions in the polymerization step were a polymerization temperature of 122° C. in the complete mixing reactor and a polymerization temperature of 120 to 142° C. in the laminar flow reactor. The devolatilized unreacted gas was condensed in a condenser through which a coolant of −5° C. was passed, and recovered as an unreacted liquid. The polymer content in the final polymerization solution was measured after drying the polymerization solution at 215°C under a reduced pressure of 2.5 kPa for 30 minutes according to the formula [(sample mass after drying / sample mass before drying)×100%], and was found to be 65.6% by mass, with an MFR of 4.6.
[0099] [Blend - 1] The HIPS-1 was mixed with 5% by mass of styrene-maleic anhydride copolymer (XIBOND250, manufactured by POLYSCOPE), and the MFR was 3.2.
[0100] [Phosphinate compound (b)] Aluminum phosphinate (also referred to as DEP-A in Tables 1 and 2) "Exolit OP1230 manufactured by Clariant Japan" Average particle size: 20 μm Aluminum phosphinate (also referred to as DEP-B in Tables 1 and 2) "Exolit OP930 manufactured by Clariant Japan" Average particle size 3 μm Aluminum phosphinate (also referred to as DEP-C in Tables 1 and 2) was produced with reference to the method described in JP-A-08-73720. Average particle size: 0.8 μm Phosphate ester: Resorcinol bis-dixylenyl phosphate [manufactured by Daihachi Chemical Industry Co., Ltd., PX-200, melting point 92°C]
[0101] [Cellulosic polysaccharides (C)] Cellulose fiber-1 (Celite, SW-10, d1: 20 μm, d2: 700 μm, lignin content 0.5%, hemicellulose content 11% by mass) Cellulose fiber-2 (Asahi Kasei Corporation, ST-02, d1: 50 μm, d2: 100 μm, lignin content 0%, hemicellulose content 0% by mass) CNF: Cellulose nanofiber (manufactured by Chuetsu Pulp Industry Co., Ltd., CNF-10, d1: 35 nm, d2: approx. 1 μm, lignin content 0%, hemicellulose content 15% by mass) Wood flour (manufactured by Naka Wood Co., Ltd., raw material: cedar, d1: 120 μm, d2: 180 μm, lignin content 23%, hemicellulose content 18% by mass) Hemicellulose (Wako Pure Chemical Industries, xylan)
[0102] [Examples 1 to 9] To a total amount of 100 parts by mass of styrene-based resin (A) and cellulose-based polysaccharide (B) having the composition ratio shown in Table 1 below, 0.2 parts by mass of Irganox1076 and Irgafos168 were added and premixed. The resulting premixes were mixed together and melt-extruded at 180°C to 220°C using a twin-screw extruder (Toshiba Machine Co., Ltd., TEM-26SS), to obtain pellets of a styrene-based resin composition as a kneaded product. At this time, the screw rotation speed was 150 rpm, and the discharge rate was 10 kg / hr. The pellet-shaped flame-retardant styrene-based resin composition thus obtained was molded using an injection molding machine manufactured by Japan Steel Works, Ltd. equipped with ISO527-2 multipurpose test piece type 1A at a cylinder temperature of 220°C, a mold temperature of 50°C, an injection pressure (gauge pressure 40-60MPa), an injection speed (panel set value) of 50%, and an injection time / cooling time of 5sec / 20sec to produce a test piece (a), and the physical properties were measured. In addition, a test piece (b) was produced under the same conditions as the above test piece (a) using a flat die with both ends gates measuring 127mm x 12.7mm x 0.8mm thick, and the flame retardancy was measured. The experimental results of Examples 1 to 9 are shown in Table 1.
[0103] [Comparative Examples 1 to 13] In Comparative Examples 1 to 13, foamed extruded sheets were obtained in the same manner as in the Examples, except that the compositions were changed as shown in Table 2. Table 2 shows the results of measurement and evaluation of each physical property.
[0104] [Table 1]
[0105] [Table 2]
[0106] As shown in Table 1 above, the flame-retardant styrene-based resin compositions obtained in Examples 1 to 9 were compositions that reduced the environmental load and were excellent in low smoke generation, flame retardancy, dimensional accuracy, and color tone. In particular, it was confirmed that the low smoke generation was improved when the composition contained an unsaturated carboxylic acid monomer and the amount of hemicellulose in the cellulose-based polysaccharide (b) was 1 mass% or more.
[0107] As shown in Table 2, low smoke generation, flame retardancy, and dimensional accuracy cannot be obtained with only the phosphinate compound (b). Furthermore, low smoke generation, flame retardancy, and dimensional accuracy cannot be obtained with only the cellulose polysaccharide (C), and discoloration due to cellulose is also significant. If the size of the cellulose polysaccharide (C) is small, dimensional accuracy cannot be obtained, and conversely, if it is too large, black smoke is generated. Furthermore, when the phosphinate compound (b) is changed to a phosphoric ester, the heat resistance is greatly reduced, and under the conditions of Table 2, it melts and the linear expansion coefficient cannot be obtained. Furthermore, if the content of the phosphinate compound (b) or the cellulose polysaccharide (C) is more than the specified amount, the fluidity is poor and molding is not possible. [Industrial Applicability]
[0108] The flame-retardant styrene-based resin composition of the present invention can be suitably used for building materials, electronic and electric parts, automobiles, food container parts, foam parts, and the like.
Claims
1. 40 to 92% by mass of a styrene-based resin (A); The following general formula (i): 【Chemistry 1】 [In the above formula (i), R i1 and R i2 are each independently unsubstituted or one or more hydrogen atoms are substituted by R i3 a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 6 to 14 carbon atoms, which may be substituted by The substituent R i3 is represented by the following formula (ii): 【Chemistry 2】 In the above formula (ii), R ii1 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and * represents a bond to another atom. M i is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion, and protonated nitrogen bases, and p is M i represents an ionic valence of 1 to 3, m i1 is a positive integer from 1 to 3, n is a positive integer from 1, 2, or 3, r is a positive integer from 1 to 3, and |p×r|=|n×m i1 |.] and a flame retardant (B) containing a phosphinate compound (b) represented by the formula: and 3 to 30% by mass of a cellulose-based polysaccharide (C) having an average minor axis d1 length of 10 to 80 μm; The average length of the minor axis d 1 is an arithmetic average of the shortest lengths of 100 cellulose polysaccharides (C) measured by observation under a transmission electron microscope (magnification: 5000 times).
2. The flame-retardant styrene-based resin composition according to claim 1, wherein the phosphinate compound (b) is at least one or more selected from the group consisting of a phosphinate represented by the following general formula (1) and a diphosphinate represented by the following general formula (2): 【Chemistry 3】 [In the above formula (1), R 11 and R 12 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; M 1 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion, and protonated nitrogen base; a is M 1 represents an ionic valence of 1 to 3; m 1 is a positive integer from 1 to 3; a=m 1 It is.] The following formula (2): 【Chemistry 4】 [In the above formula (2), R 21 and R 22 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms; L 23 is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 14 carbon atoms, or an arylalkylene group having 6 to 14 carbon atoms; M 2 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion, and protonated nitrogen bases; b is M 2 represents an ionic valence of 1 to 3, m 2 is a positive integer from 1 to 3, q is a positive integer of 1 or 2, and b×q=2m 2 It is.]
3. The flame-retardant styrene-based resin composition according to claim 1 or 2, wherein the styrene-based resin (A) contains a styrene-based monomer unit and an unsaturated carboxylic acid-based monomer unit.
4. The flame-retardant styrene-based resin composition according to any one of claims 1 to 3, wherein the cellulose-based polysaccharide (C) is a cellulose containing 20 mass% or less of lignin.
5. The flame-retardant styrene-based resin composition according to any one of claims 1 to 4, characterized in that the cellulose-based polysaccharide (C) has a hemicellulose content of 1% or more.
6. A molded article comprising the flame-retardant styrene-based resin composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Synergistic flame retardant combination for polymer
JP1999124466A
Laminated film
JP2010149447A
Resin composition and manufacturing method therefor
JP2011144210A
Method for producing modified cellulose
JP2021006628A
Flame-retardant styrenic resin composition and molding
JP2023020705A